No common pesticides detected in snow buntings utilizing a farmland landscape in eastern Québec - Ruhs, Emily Cornelius; Love, Oliver P.; Drainville, Louis; Vézina, François (Avian Conservation and Ecology, 2021)
Many species of migratory birds are declining worldwide, including throughout North America. Some of the most cited causes of decline are linked to climate change, urbanization, and growth in agriculture. Across eastern Canada, a number of insecticides and herbicides are commonly sprayed before and during the grain growing season to control pests and foliage competitors. During wintering and migration, a declining Arctic-breeding songbird, the snow bunting (Plectrophenax nivalis), utilizes open farmlands of southern Canada; therefore, this could be a period when the species is most exposed to these pesticides. We tested snow bunting tissues (blood and liver) for the 4 pesticides most commonly used in grain agriculture in Canada: atrazine, chlothianidin, imidacloprid, and glyphosate, as well as a glyphosate derivative (aminomethylphosphic acid, AMPA). Although this species is thought to forage in grain fields during autumn through spring, we found no detectable traces of any of the five substances. Wintering buntings may either not be exposed to these pesticides during their presence in agriculture fields or, given the rapid turnover of these pesticides in the blood and tissues, be exposed to doses below detection level in samples.